Clinical Significance of Serum Hemeoxygenase-1 as a New Biomarker for the Patients with Interstitial Pneumonia - Kota Murohashi; Yu Hara; Kanako Shinada; Kenjiro Nagai; Masaharu Shinkai; Akihiko Kawana; Takeshi Kaneko (Canadian Respiratory Journal)
Background. Serum hemeoxygenase-1 (HO-1) has been proposed to be a biomarker of lung disease activity and prognosis. The present study aimed at evaluating whether HO-1 could be a useful marker for evaluating disease activity and predicting prognosis in patients with interstitial pneumonia (IP). Materials and Methods. Serum HO-1 levels of newly diagnosed or untreated patients with IP were measured at hospitalization. We evaluated the relationships between serum HO-1 and other serum biomarkers, high resolution CT (HRCT) findings, and hospital mortality. Results. Twenty-eight patients with IP, including 14 having an acute exacerbation (AE) and 14 not having an AE, were evaluated. The patients having an AE had significantly higher HO-1 levels than those not having an AE (53.5 ng/mL vs. 24.1 ng/mL; p<0.001), and the best cut-off level to discriminate between having an AE or not having an AE was 41.6 ng/mL. Serum HO-1 levels were positively correlated with serum levels of surfactant protein-D (r=0.66, p<0.001) and the ground glass opacity score (calculated from HRCT; r=0.40, p=0.036). Patients who subsequently died in hospital had presented with significantly higher HO-1 levels than those who did not die in hospital (64.8 ng/mL vs. 32.0 ng/mL; p=0.009). Conclusion. Serum HO-1 may serve as a useful biomarker for detecting AE or predicting hospital mortality in patients with IP.